MANAJEMEN SEKOLAH DALAM MEREALISASIKAN RELIGIOUS CULTURE DI SMPN 1 BATUKLIANG LOMBOK TENGAH - Nurul Hasani; Ahmad Sulhan; Subki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Each school has its own unique school culture. This study aims to analyze culture and school management in realizing religious culture. The research design uses qualitative research. The location chosen as the research location is SMPN 1 Batukliang. The method chosen as the data collection technique is observation, structured interviews, and documentation. The main informants in this study were madrasa heads, teachers, and administration. Checking the validity of the data used is a member check then combined with triangulation, presenting data, and drawing conclusions. The results of the study show that the religious culture that is applied is the existence of social harmony which can be seen from the 5S attitude, strengthening the internalization of religious rituals in schools, and developing religious symbols through commemoration of Islamic holidays). School management is carried out following the management function itself, starting from planning (internal and external assessments and formulating the vision and mission of the school), organizing (job descriptions or placement of existing resources), directing (implementation of all plans), and evaluation (deliberations conducted on a scheduled or incidental basis).